(untitled) (Global Journal of Science Frontier Research, 2021)
A system for continuous monitoring of the state of insulation and the whole transformer under operating conditions, in addition to standard means for measuring and monitoring the state of transformers, interference-proof high-frequency channels from PIN inputs, from the grounding of the tank and electroacoustic channels for both partial discharges and for detecting mechanical damages, winding displacements, magnetic circuit barriers and other transformer, units that are not detected by other methods, has been developed.